Strategi Promosi Terhadap Peningkatan Volume Penjualan Pada Toko Redjo AC Sukoharjo - Hasanudin Hasanudin; Esti Dwi Rahmawati; Agus Suyatno (Jurnal Bintang Manajemen, 2023)
The market for the need for electronic goods such as air conditioners is much sought after by the public, which is marked by the large number of dealers or electronics stores that sell air conditioners. This has the impact of causing competition between business actors to attract consumers to buy. In this study the method used by researchers used data collection methods through observation, interviews, and documentation directly in the field, with qualitative descriptive analysis techniques and SWOT analysis using SWOT matrix analysis tools. The purpose of this research is to find out the promotion strategy that is run by Redjo AC store and the right promotion strategy to use it. The right promotion strategy to be carried out by the Redjo AC Sukoharjo store is a direct marketing promotion strategy because it will make consumers feel served by their air conditioning needs, what consumers want will be what they want and will make consumers loyal and will recommend to others